Pectina de Citrus sinensis como viscosificante en fluidos de perforación poliméricos - Barreto, Steevenson; Castillo Campos, Luis (Latin American Journal of Energy Research, 2021)
The present investigation was based on the experimental evaluation of the orange-based pectin (Citrus sinensis) as a viscosifier agent in polymeric drilling fluids. To develop the additive, the orange fruit peels were subjected to hydrolysis with citric acid, and then this solution was precipitated with ethanol and the resulting hydrogel was chemically and physically characterized. In the subsequent stage, fluid samples were formulated with xanthan gum and pectin to compare their performance through experimental laboratory procedures governed by API 13-B1. Finally, an Analysis of Variance was applied to determine the means that are significantly different from each other between the commercial product and the one proposed, through the Statgraphics program. In conclusion, it was obtained that pectin showed a statistically similar behavior, although inferior to xanthan gum as a viscosifier additive in polymeric drilling fluids, considering as a variant the expansion of its concentration for fluid rheology optimal development.